Blood pressure and risk of cancer in the European Prospective Investigation into Cancer and Nutrition. Issue 10 (20th August 2019) - Christakoudi, Sofia; Kakourou, Artemisia; Markozannes, Georgios; Tzoulaki, Ioanna; Weiderpass, Elisabete; Brennan, Paul; Gunter, Marc; Dahm, Christina C.; Overvad, Kim; Olsen, Anja; Tjønneland, Anne; Boutron‐Ruault, Marie‐Christine; et al.
Abstract : Several studies have reported associations of hypertension with cancer, but not all results were conclusive. We examined the association of systolic (SBP) and diastolic (DBP) blood pressure with the development of incident cancer at all anatomical sites in the European Prospective Investigation into Cancer and Nutrition (EPIC). Hazard ratios (HRs) (95% confidence intervals) were estimated using multivariable Cox proportional hazards models, stratified by EPIC‐participating center and age at recruitment, and adjusted for sex, education, smoking, body mass index, physical activity, diabetes and dietary (in women also reproductive) factors. The study included 307, 318 men and women, with an average follow‐up of 13.7 (standard deviation 4.4) years and 39, 298 incident cancers. We confirmed the expected positive association with renal cell carcinoma: HR = 1.12 (1.08–1.17) per 10 mm Hg higher SBP and HR = 1.23 (1.14–1.32) for DBP. We additionally found positive associations for esophageal squamous cell carcinoma (SCC): HR = 1.16 (1.07–1.26) (SBP), HR = 1.31 (1.13–1.51) (DBP), weaker for head and neck cancers: HR = 1.08 (1.04–1.12) (SBP), HR = 1.09 (1.01–1.17) (DBP) and, similarly, for skin SCC, colon cancer, postmenopausal breast cancer and uterine adenocarcinoma (AC), but not for esophageal AC, lung SCC, lung AC or uterine endometroid cancer. We observed weak inverse associations of SBP with cervical SCC: HR = 0.91 (0.82–1.00) and lymphomas: HR = 0.97 (0.93–1.00). There were no consistent associations with cancers in other locations. Our results are largely compatible with published studies and support weak associations of blood pressure with cancers in specific locations and morphologies. Abstract : What's new? Is there a link between high blood pressure and cancer? In this large, prospective study, the authors found that hypertension is indeed associated with a moderate increase in risk for several cancers, including renal, esophageal (only squamous cell carcinoma), head and neck, skin, colon, post‐menopausal breast cancer, and uterine cancer (only adenocarcinoma). These results may potentially enhance screening and risk assessment. Further research may also identify shared mechanisms for both hypertension and cancer, such as inflammation, lipid peroxidation, etc.